(untitled) (Research, Society and Development, 2021)
The main objective of the present work is to investigate gender issues in the context of the history of rivalries between state schools in Belem-Pa, which is currently configured as a problem notably of school violence. In view of this initiative, the guiding question of the study is to know: What are the meanings and images produced in newspaper articles from the 1970s, within the scope of the mediatization of school civic parties in Belem-Pa, about young female students and their relationship with the social context of the historical period under analysis? Based on documental research, whose corpus consists of eighteen (18) printed media materials from the 1970s. Whose analysis was conducted in the light of the analysis of meaning according to the Bakhtinian theory. It was observed that there were different social roles for young girls and boys, which demonstrates a socio-educational training project based on gender issues and inequalities. For young females, training for marriage and social entertainment; and for young boys a masculine ethos, virility, being rational, intelligent, and training for positions of command and leadership. Therefore, it is expected to contribute with material and historical subsidies to better understand the construction of the image of women - young students - from the media fabric and its relationship with the socio-educational context experienced during the dictatorial period, and thus lead back to the history of education in the State of Pará.